Sustained impact of an antibiotic stewardship initiative targeting asymptomatic bacteriuria and pyuria in the emergency department - Mary Catherine Cash; Garrett Hile; James Johnson; Tyler Stone; Jessica Smith; Chris Ohl; Vera Luther; James Beardsley (Cambridge University Press, 2022)
Abstract Objective: To determine whether a multifaceted initiative resulted in maintained reduction in inappropriate treatment of asymptomatic pyuria (ASP) or bacteriuria (ASB) in the emergency department (ED). Design: Single-center, retrospective study. Methods: Beginning in December 2015, a series of interventions were implemented to decrease the inappropriate treatment of ASP or ASB in the ED. Patients discharged from the ED from August to October 2015 (preintervention period), from December 2016 to February 2017 (postintervention period 1), and from November 2019 to January 2020 (postintervention period 2) were included if they had pyuria and/or bacteriuria without urinary symptoms. The primary outcome was the proportion of patients prescribed antibiotics within 72 hours of discharge from the ED. The secondary outcome was the number of patients returning to the ED with symptomatic UTI within 30 days of discharge. Results: We detected a significant decrease in the proportion of patients with ASP or ASB who were inappropriately treated when comparing the preintervention group and post-intervention group 1 (100% vs 32.4%; P < .001). This reduced frequency of inappropriate treatment was noted 3 years after the intervention, with 28% of patients receiving treatment for ASP or ASB in postintervention group 2. (P was not significant fin the comparison with postintervention group 1.) Among the 3 groups analyzed, we detected no difference in the numbers of patients returning to the ED with a symptomatic UTI within 30 days of ED discharge regardless of whether patients received antibiotics. Conclusions: A multifaceted intervention resulted in a significant decrease in inappropriate use of antibiotics for ASP and/or ASB that was maintained 3 years after implementation.